2013
DOI: 10.2527/jas.2012-5470
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic relationships of feed efficiency with growth performance, ultrasound, and carcass merit traits in Angus and Charolais steers1

Abstract: Feed efficiency is of particular importance to the beef industry, as feed costs represent the single largest variable cost in beef production systems. Selection for more efficient cattle will lead to reduction of feed related costs, but should not have adverse impacts on quality of the carcass. In this study, we evaluated phenotypic and genetic correlations of residual feed intake (RFI), RFI adjusted for end-of-test ultrasound backfat thickness (RFIf), and RFI adjusted for ultrasound backfat thickness and LM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
65
6
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 20 publications
18
65
6
5
Order By: Relevance
“…Similarly, McDonagh et al (2001), using steers, Lancaster et al (2009), using bulls, andCruz et al (2010), using steers, Visceral organ and carcass traits in bulls differing in RFI found that RFI had no effect on M. longissimus dorsi area (LMA) in beef cattle consuming a high concentrate diet. Mao et al (2013) also found that RFI had weak or close to zero phenotypic correlations with LMA in Angus and Charolais steers however, genetic correlations between RFI and LMA in both breeds were positive and weak to moderate. The absence of an effect of RFI on LD depth and area in the current and other studies suggests that size of lean muscle tissue may not be the sole contributor to variation in RFI and that biological processes within muscle tissue such as protein turnover and tissue metabolism may have pivotal roles in improved feed efficiency (Herd and Arthur, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, McDonagh et al (2001), using steers, Lancaster et al (2009), using bulls, andCruz et al (2010), using steers, Visceral organ and carcass traits in bulls differing in RFI found that RFI had no effect on M. longissimus dorsi area (LMA) in beef cattle consuming a high concentrate diet. Mao et al (2013) also found that RFI had weak or close to zero phenotypic correlations with LMA in Angus and Charolais steers however, genetic correlations between RFI and LMA in both breeds were positive and weak to moderate. The absence of an effect of RFI on LD depth and area in the current and other studies suggests that size of lean muscle tissue may not be the sole contributor to variation in RFI and that biological processes within muscle tissue such as protein turnover and tissue metabolism may have pivotal roles in improved feed efficiency (Herd and Arthur, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However Crowley et al (2011), found that the genetic correlation between RFI and carcass fat score was positive (r = 0.33) and Mao et al (2013), found that the genetic correlation between RFI and carcass grade fat was positive (r = 0.42) in Charolais steers but was close to zero (r = 0.02) in Angus steers. Differences in the propensity for fat accreation between different beef breeds, coupled with variation in carcass fat determination, may be contributing to the contrasting genetic correlations between RFI and carcass fatness observed between studies.…”
Section: Discussionmentioning
confidence: 99%
“…The animal populations, the management of the herds and the descriptive statistics of the five carcass merit traits were reported previously (Mao et al . ).…”
Section: Realized Accuracy (± Se) Of Genomic Breeding Values Of Carcamentioning
confidence: 97%
“…The RFI records for dairy cattle were of 842 Australian Holstein heifers measured at about 6 mo of age (Pryce et al, 2012). The Canadian beef cattle RFI phenotypes consisted of 534 Angus, 384 Charolais (Mao et al, 2013;Chen et al, 2013), and 1,845 mixed synthetic breed (that consisted of the following average breed composi- Abo-Ismail, 2011;Lu et al, 2012). The Holstein heifers and 820 Angus cattle from the New South Wales Department of Primary Industry's Research Centre at Trangie, NSW, Australia, were fed an alfalfa pelleted diet and measured at about 9 mo of age, while the other cattle were fed a finishing feedlot diet and measured at older ages (between 10 and 18 mo of age).…”
Section: Phenotype Datamentioning
confidence: 99%